HUBUNGAN ANTARA TINGKAT PENDIDIKAN DENGAN KEPATUHAN PROTOKOL KESEHATAN COVID-19 PADA LANSIA - RAHMAD SEPTIAN REZA (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Health protocols during a pandemic are important to be used as the basis for the government's approach to compliance with health protocols. The results of the observation are that from 10 people there are 5 people who don't wear masks and 5 others obey, there are 8 people who don't wash their hands and 2 others are obedient, there are 7 who don't keep their distance and 3 others are obedient. The purpose of the study was to analyze the relationship between education level and Covid-19 health protocol compliance in the elderly. This study used a cross sectional design. The independent variable is the level of education and the dependent variable is the compliance with the Covid-19 health protocol. The study population was 98, a sample of 78 elderly using Simple Random Sampling technique. The research instrument used a questionnaire with the Spearman Rank test whit α = 0,05. The results showed that most of the basic education levels were 41 (52.6%), almost half of the Covid-19 health protocol compliance level with the non-compliant category was 36 (46.1%). Based on the results of the statistical test with the Spearman rank test, the results obtained p value: 0.024 < < : 0.05 so Ha is accepted, meaning that there is a relationship between education level and Covid-19 health protocol compliance in the elderly. The solution to overcome the compliance of the Covid-19 health protocol in the elderly is advised to have self-awareness of each individual, the role of community leaders to improve compliance with the Covid-19 health protocol properly to protect themselves from the dangers of Covid-19.